Charismatic chaos - MacArthur, John F. Jr, 1939- (Grand Rapids, MI Zondervan, 1992)
Includes bibliographical references and indexes.
Keywords: Pentecostalism -- controversial literature; Gifts, spiritual -- biblical teaching